2020
DOI: 10.3390/ijms21155268
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of the SANT/Myb Domain of FLASH and YARP Proteins and Their Complex with the C-Terminal Fragment of NPAT by NMR Spectroscopy and Computer Simulations

Abstract: FLICE-associated huge protein (FLASH), Yin Yang 1-Associated Protein-Related Protein (YARP) and Nuclear Protein, Ataxia-Telangiectasia Locus (NPAT) localize to discrete nuclear structures called histone locus bodies (HLBs) where they control various steps in histone gene expression. Near the C-terminus, FLASH and YARP contain a highly homologous domain that interacts with the C-terminal region of NPAT. Structural aspects of the FLASH–NPAT and YARP–NPAT complexes and their role in histone gene expression remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Interestingly, GON4L/YARP binds to the same 31 amino acids at the very C terminus of NPAT that FLASH does. GON4L/YARP and FLASH use similarly structured SANT/Myb domains containing a bundle of three alpha helices that each binds to NPAT in a slightly different orientation [ 40 ]. NMR structural studies indicate that these binding events are mutually exclusive, setting up an interesting possible scenario in vivo in which multiple different NPAT complexes with different functional roles reside with the HLB.…”
Section: Composition and Function Of Histone Locus Bodiesmentioning
confidence: 99%
“…Interestingly, GON4L/YARP binds to the same 31 amino acids at the very C terminus of NPAT that FLASH does. GON4L/YARP and FLASH use similarly structured SANT/Myb domains containing a bundle of three alpha helices that each binds to NPAT in a slightly different orientation [ 40 ]. NMR structural studies indicate that these binding events are mutually exclusive, setting up an interesting possible scenario in vivo in which multiple different NPAT complexes with different functional roles reside with the HLB.…”
Section: Composition and Function Of Histone Locus Bodiesmentioning
confidence: 99%
“…This area is the largest in terms of the number of related publications and includes 91 articles, namely [ 1 , 2 , 3 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ,…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…Studies have shown that NPAT/Mxc acts as the scaffold protein of the HLB required for HLB assembly and transcription of canonical histone genes [ 5 ]. The N-terminal of NPAT/Mxc is crucial for self-interaction, while the C-terminal is required for recruiting other members of the HLB [ 9 , 10 ]. NPAT/Mxc is phosphorylated by cyclin E/Cdk2, such phosphorylation being a key factor in the formation of phase separation allowing the formation of HLB to be precisely and dynamically regulated [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%